Restriction of Civil Liability for Beneficial Owners in Bankruptcy Disputes Arising from Homologation Default: An Analysis of the Separate Corporate Veil Doctrine - Keisha Nadine Sastraatmaja; Laela Kuwayyis Wijaya; Maheswari Queena Dewani; Thenezia Tania Tirajoh; Valence Deanthony Dior; Wilhelmina Setia Atmadja (SIGn Jurnal Hukum, 2026)
The bankruptcy of PT Sritex, resulting from a homologation default, has sparked a debate over creditors’ efforts to demand liability beyond the protective boundaries of the corporate entity. This research aims to critically examine the limitations of separate corporate veil protection and analyze the position of beneficial owners in bankruptcy disputes arising from debt restructuring failure. Through normative legal research employing statutory, conceptual, and case approaches, the analysis is conducted deductively using the legal hermeneutics method to examine civil regulatory instruments. The research findings show that the annulment of homologation constitutes a mere civil default that does not immediately deprive the legal entity of its independence. Contract creditors are hindered by an absolute burden of proof, under which the piercing of the corporate veil doctrine is rejected without material evidence of unlawful acts or the misuse of the corporate entity. Furthermore, the beneficial owner status is dogmatically identified exclusively as an administrative compliance instrument within the public law domain. This administrative determination lacks the juridical force to annul the limited liability principle in civil bankruptcy without the proof of actual loss causality. In conclusion, the debt liability of a bankrupt company cannot be automatically imposed on the personal wealth of shareholders or beneficial owners. This legal certainty demands that the judiciary tighten evidentiary standards to protect the limited-risk investment climate in Indonesia.